Distribution of sediment chlorophyll-a and phaeopigments in the brackishwater ponds along the Nethravathi estuary, India - Rajesh, K M; Gowda, Gangadhara; Menon, Mridula R; Nazareth, A P (Indian Journal of Fisheries, 2011)
Chlorophyll-a and phaeopigments were studied for 12 months from February1998 to January 1999 in the brackishwater ponds along Nethravathi estuary,Mangalore. Chlorophyll-a values fluctuated from 0.04 mg/g (August) to 1.92 mg/gdry sediment (May). It exhibited trimodal distribution with primary peak duringMay, secondary peak during December and tertiary peak in September.Phaeopigment concentration varied from 0. 18mg/g to 3 1.71mg/g dry sediment.Chlorophyll-a showed significant correlation with temperature and micro algaein the sediment, however an inverse relation was observed between Chlorophyll- aand phaeopigments.